Osteoid osteoma - Manjunatha B; Nagarajappa D (Wolters Kluwer Medknow Publications, 2009)
Osteoid osteoma is a benign tumor of the bone which arises from osteoblasts and is extremely rare in jaws. Only 15 cases of osteoid osteoma have been reported in English-language literature. This case report is presented here due to its rarity.